Analisis Hukum Pidana dalam Penanggulangan Kekerasan dalam Rumah Tangga (KDRT) - Ruth Yessika Siahaan; Salwa Andini; Reh Bungana Br. PA; Maulana Ibrahim (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Domestic violence (KDRT) is a serious problem that requires appropriate legal handling. This article aims to analyze aspects of criminal law in dealing with cases of domestic violence. The research method used is literature study by collecting data from various trusted sources such as journals, articles and other sources. The results of the analysis show that handling cases of domestic violence must be carried out firmly and fairly in accordance with applicable criminal law. Apart from that, prevention efforts also need to be made through education and outreach to the public about the importance of respecting human rights and avoiding acts of domestic violence. It is hoped that the results of this research can make a positive contribution to law enforcement and overcoming cases of domestic violence in Indonesia.